Misi Gereja di Era Kapitalisme Global: Eksplorasi Pelayanan Misi Yesus: The Church’s Mission In The Era Of Global Capitalism: An Exploration On The Mission Model In Jesus’ Ministry - Yohanes Hasiholan Tampubolon (Societas Dei: Jurnal Agama dan Masyarakat, 2020)
Churches needs to consider how to do mission in the era of global capitalism. The negative impact of the current global capitalism epoch is created by economic and political gaps. Massive destruction of nature is also an impact of global capitalism. The topic will be elaborated through a literature research. The church faces a dif-ferent type of global reality in each age; however, it can learn from Jesus ministry. Jesus’ ministry showed concern for the poor, the marginalized and the helpless. Jesus is not someone who does not care about economic and political issues. The ministry carried out also has relevance to the individual and structural life. There is no structural change without individual changes (and vice versa). The church also needs to build a collective network to strive for a better life. Keywords: mission; global capitalism; ministry; Jesus.